Event-triggered feedback control with one-bit transmission - Muhammad Mirza Zulkifli (2019)
In this report, a proposal of an event-trigger feedback control design for a class of uncertain nonlinear systems is introduced. This type of system is made up of unknown system parameters and mostly nonlinear functions, which can be found in today’s modern physical systems. This report examines fundamental theories in control systems, adaptive control and recursive backstepping control design which lay the foundations for introducing the 2 strategies for the event-trigger control design, the fixed threshold and the relative threshold strategy, in which both are presented with the assumption of input-to-state (ISS) is held. These strategies are mathematically formed using the adaptive backstepping method and proven using Lyapunov analyses. Also, this report also introduces an encoder-decoder strategy where it uses binary (1 or 0) to transmit whether an event is to be triggered and updated. This strategy is overcome the problem of limited bandwidth constraints. An implementation of this control scheme is formed through MATLAB/Simulink based simulations. This report also studies the effects of key system parameters based on these control design strategies and proposes recommendations for system tuning based on the behavior of the system signals.